Debate teórico sobre el proceso de instalaciónde una cultura de la violencia en Venezuela - Freddy A. Crespo P. (Revista Criminalidad)
The current work aims to analyze and debate theoretically the social changes and the responses to these in Venezuela. These social changes directly affected the social processes in which violence was included within the social dynamics and interaction and general moral of Venezuelan society, presenting itself to the individual as a valid behavior to relate to other people and to the social structure in general. Therefore, the theoretical discussion is proposed in which the notions of different disciplines are expanded and interpreted, in order to sustain that in Venezuela, this social process of assimilation of violence in the general social dynamic led to the installation of a Culture of Violence and this, at the same time, fed the violent action by extending it both qualitatively and quantitatively in Venezuelan society. It is concluded that different social and institutional factors produced a failure in Venezuelan social system to sustain the validity of the norm and culturally and institutionally acceptable behavior. As a consequence, violence entered the social structure and, not being effectively sanctioned, it was legitimized as an acceptable behavior for obtaining social gratifications, while at the same time institutions were delegitimized, causing violence to be presented as a socially accepted action for the individual and even for the same institutions, thus promoting a generation of individuals more socially prone to violence.